WETON SEBAGAI KEARIFAN LOKAL DALAM KEHIDUPAN MASYARAKAT DI DESA CANTUK KABUPATEN BANYUWANGI - Tofan Priananda Adinata; Putri Umulatifah; Dhalia Soetopo (Keraton: Journal of History Education and Culture, 2026)
The Weton tradition in Cantuk Village is a form of local wisdom that integrates into five aspects of life; however, its existence is threatened due to a decline in philosophical understanding among the younger generation in the digital era. This study aims to describe the philosophical meaning and implementation of Weton, as well as to analyze the process of its inheritance and adaptation in the Society 5.0 era. Using a descriptive qualitative approach, this study involved 45 informants across four hamlets selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation, then analyzed interactively using the Miles, Huberman, and Saldana model. Max Weber’s Social Action theory and Cultural Adaptation theory were employed as analytical frameworks. The results show that Weton functions as a mechanism for risk management and life harmony. Although the inheritance process has shifted toward digital media, the validation of philosophical values still relies on the authority of elders through intergenerational dialogue. This phenomenon reflects the resilience and techno-cultural hybridity of the community in maintaining Weton as an adaptive identity.